Analysis of the Use of Codon Pairs in the He Gene of the Isa Virus Shows a Correlation Between Bias in Hpr Codon-Pair Use and Mortality Rates Caused by the Virus - Spencer-Ossa, E; Tello-Reyes, M (2013)
Sin Editorial Disponible